2011
DOI: 10.1007/s11655-011-0845-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chinese medicine constitution susceptibility to diabetic nephropathy and transforming growth factor-β1 (T869C) gene polymorphism

Abstract: Chinese medicine constitutions were associated with TGF-β1 (T869C) gene polymorphism, a potential predictor of susceptibility to DN in T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Only a significantly increased frequency of the C allele and CC genotype of the T869C polymorphism was observed in patients with nephropathy, suggesting the association of this polymorphism with an increased risk of T2D renal complication. Similar results were observed by Mou et al [38] that investigated the T869C polymorphism in 180 T2D Chinese patients with nephropathy in stages III, IV, and V, besides 180 patients without this complication. They also reported that CC/CT genotypes were associated with an increased risk of worsening renal function.…”
Section: Tgf-1 Gene Polymorphisms and Diabetic Nephropathysupporting
confidence: 87%
“…Only a significantly increased frequency of the C allele and CC genotype of the T869C polymorphism was observed in patients with nephropathy, suggesting the association of this polymorphism with an increased risk of T2D renal complication. Similar results were observed by Mou et al [38] that investigated the T869C polymorphism in 180 T2D Chinese patients with nephropathy in stages III, IV, and V, besides 180 patients without this complication. They also reported that CC/CT genotypes were associated with an increased risk of worsening renal function.…”
Section: Tgf-1 Gene Polymorphisms and Diabetic Nephropathysupporting
confidence: 87%
“…Eight studies [ 12 , 32 , 69 74 ] reporting the association of the TGF-β1 T869C gene polymorphism with susceptibility to T2DN were included in this study. Two report [ 69 , 74 ] were published using the English language and the other reports were published using Chinese. The data for the pooled OR were extracted (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationships between BC and DM [ 32 , 33 ], insulin resistance [ 34 ], diabetic nephropathy [ 35 ], and diabetic peripheral arterial disease [ 36 ] have been established, thus confirming TCM patient classification theory and verifying a new TCM treatment strategy for DM [ 37 ]. However, the association between BC and DR has yet to be determined.…”
Section: Introductionmentioning
confidence: 88%